2017
DOI: 10.1002/hbm.23854
|View full text |Cite
|
Sign up to set email alerts
|

Social comparison in the brain: A coordinate‐based meta‐analysis of functional brain imaging studies on the downward and upward comparisons

Abstract: Social comparison is ubiquitous across human societies with dramatic influence on people's well-being and decision making. Downward comparison (comparing to worse-off others) and upward comparison (comparing to better-off others) constitute two types of social comparisons that produce different neuropsychological consequences. Based on studies exploring neural signatures associated with downward and upward comparisons, the current study utilized a coordinate-based meta-analysis to provide a refinement of under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(53 citation statements)
references
References 205 publications
(305 reference statements)
1
51
0
1
Order By: Relevance
“…In contrast to the existence of disadvantageous-inequity aversion across species, advantageous-inequity aversion has thus far only been observed in human and nonhuman species with extensive cooperation outside of kinship relationships (5). Therefore, it is conceivable that the processing of advantageous inequity may require brain structures involved in mentalizing [e.g., dorsomedial prefrontal cortex (DMPFC)] (15), norm violation detection (e.g., aINS) (16)(17)(18)(19)(20), and cognitive control [e.g., dorsolateral prefrontal cortex (DLPFC)] (21), in addition to regions representing values of relative gain (e.g., ventral striatum) (22).…”
Section: Significancementioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to the existence of disadvantageous-inequity aversion across species, advantageous-inequity aversion has thus far only been observed in human and nonhuman species with extensive cooperation outside of kinship relationships (5). Therefore, it is conceivable that the processing of advantageous inequity may require brain structures involved in mentalizing [e.g., dorsomedial prefrontal cortex (DMPFC)] (15), norm violation detection (e.g., aINS) (16)(17)(18)(19)(20), and cognitive control [e.g., dorsolateral prefrontal cortex (DLPFC)] (21), in addition to regions representing values of relative gain (e.g., ventral striatum) (22).…”
Section: Significancementioning
confidence: 99%
“…Therefore, we suggest these activations of reward-related areas actually reflected the experienced or expected pleasure of the changes in the unequal distributions, not the reactions to inequity itself. Despite this, the absence of reward-related regions in the advantageous frame seems puzzling, given that a number of studies on social comparison showed the activation of VS and VMPFC when participants performed better or attained better outcomes than others in competitive environments (22). One possible explanation is that, in those studies, individuals were satisfied with the advantageous outcomes due to the context of competition.…”
Section: Neural Correlates Of Context-dependent Advantageous-inequitymentioning
confidence: 99%
“…Furthermore, the insula is a key node of the salience network (Menon and Uddin, 2010) and processes ascending interoceptive and visceromotor signals (Ronchi et al, 2015). The insula is regarded as a central area involved in emotional processing and social cognition (Couto et al, 2013), including the detection of salience of social stimuli or events (Chen et al, 2009;Feng et al, 2015;Luo et al, 2018). Therefore, the involvement of the insula during the anticipation of social rewards and punishment avoidance in the SID task is compatible with an overall role of the insula in the autonomic activation (arousal) associated with the anticipation of salient social incentives (Schneider et al, 2018).…”
Section: Brain Regions Involved In the Anticipation Of Social Rewardsmentioning
confidence: 99%
“…A recent fMRI meta-analysis on social comparisons supports the idea that social comparisons are associated with activity in the reward network (Luo et al, 2018). The authors revealed reward-related brain regions (bilateral ventral striatum) associated with downward comparisons (i.e., comparing self with a lower level individual) and loss-related brain regions, including the bilateral insula and anterior cingulate cortex (ACC) associated with upward comparisons (i.e., comparing self with a higher level individual).…”
Section: Introductionmentioning
confidence: 90%
“…Along with the prefrontal cortex, the ventral striatum is said to have a specific role in downward comparisons during which a person with higher status or larger gains is compared with an opponent (Dvash, Gilam, Ben-Ze'ev, Hendler, & Shamay-Tsoory, 2010;Cikara, Botvinick, & Fiske, 2011;Meshi, Morawetz, & Heekeren, 2013;Lindner et al, 2015; also see Luo, Eickhoff, Hétu, & Feng, 2018 for meta-analysis). This area has been hypothesized to reflect reward-related activation analogous to the striatal-cortical encoding of reward (Lindner et al, 2015;Luo et al, 2018).…”
Section: Introductionmentioning
confidence: 99%